PUBLIC CONTROL OVER THE ACTIVITIES OF LAW ENFORCEMENT BODIES: FOREIGN EXPERIENCE AND DOMESTIC REALITIES - Бабіков, Олександр Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Objective: analysis of forms of civil control over the activities of law enforcement agencies of Ukraine. Research methods: the research was conducted using general scientific methods, such as dialectical analysis and synthesis, abstraction, etc. and special methods by which the author analyzes the forms of civil control over the activities of law enforcement agencies of Ukraine. Results: the article examines the effectiveness of various forms of civil control in the field of law enforcement and compares such activities with the experience of the EU and the US. In particular, the control of US intelligence agencies, which includes the CIA, FBI NSA and others (a total of 15 bodies) is entrusted to parliamentary committees and is carried out in the following areas: consideration of the draft intelligence community budget and control over spending, development of legislation in intelligence activities; overseeing covert operations, approving presidential nominations for director and first deputy director of the CIA, and military intelligence chiefs, preparing reports for the relevant chambers of Congress on specific issues in which intelligence played a significant role. In the Republics of Poland, Romania, Norway, civil control over the activities of intelligence (law enforcement) bodies is also exercised by parliamentary committees with control measures, assessment of their effectiveness, ensuring human and civil rights and freedoms and disclosure within the interests of the state. reports, conclusions and information. Discussion: research of the role of the public in exercising control over law enforcement agencies of Ukraine through the prism of foreign and international experience. The role of public organizations is, of course, important for building the rule of law as a means of dialogue between government agencies and society. However, if civil control is exercised through public authorities, local governments, elected or formed by the majority of our society, the activities of various public associations are formed on other principles and financed from sources that are neither controlled by the state nor under the control of society. Introduction of forms of civil control used in NABU, NAPC, DBR pose a threat of pressure from members of such public councils and public organizations that formed them, on the heads and employees of law enforcement agencies.